Faith in the familiar religion, spirituality, and place in the south of the Netherlands - Knibbe, Kim E. (Boston : Brill, 2013)
Faith in the familiar is an ethnography of religious change in the Netherlands, discussing Catholicism and popular forms of New Age. It focuses on the location of religion in local life and how people relate to religious authority.
Includes bibliographical references and indexes.
Print version record.
Keywords: Catholic Church -- Netherlands -- Limburg -- History -- 20th century; Catholic Church -- Netherlands -- Limburg -- History -- 21st century; Catholic Church; Catholic Church; Limburg (Netherlands) -- Religion -- 20th century; Limburg (Netherlands) -- Religion -- 21st century; Secularization -- Netherlands -- Limburg -- History -- 20th century; Secularization -- Netherlands -- Limburg -- History -- 21st century; SOCIAL SCIENCE -- Sociology of Religion; Religion; Secularization; Netherlands -- Limburg; Geloofsleven; Zuid-Nederland.; 1900-2099; Electronic books; History; Geschiedenis (vorm); Electronic books